Integrated Financial Management Information System: Exploring Implementation Challenges and Benefits in Organizational Contexts - Dwi Nita Aryani (Westscience Press, 2023)
This research investigates the challenges and benefits of implementing an Integrated Financial Management Information System (IFMIS) in the context of large-scale enterprise business organizations. Through a mixed-methods approach, including qualitative interviews and quantitative surveys, the study uncovers insights into the intricacies of IFMIS adoption. The qualitative phase reveals technological complexities, change management challenges, and data security concerns as key hurdles. Conversely, the benefits encompass enhanced decision-making, operational efficiency, and financial transparency. The quantitative phase substantiates these findings, affirming the significance of these challenges and benefits. The discussion of the results underscores the practical implications for organizations considering IFMIS implementation. Ultimately, this research contributes to the knowledge landscape by providing actionable insights that inform strategic decisions in the realm of financial management and technology adoption.